2009
DOI: 10.1179/joc.2009.21.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of Moxifloxacin on Exponential and Stationary Phase Cultures ofMycobacterium tuberculosis

Abstract: The bactericidal activity of moxifloxacin, alone and in combination with isoniazid and rifampin, was studied on exponential and stationary phase cultures of Mycobacterium tuberculosis H37 Rv strain, the standard strain which is a wild type of M. tuberculosis strain, not exposed to any environment, susceptible to all anti-tuberculosis drugs. Moxifloxacin alone was highly bactericidal, being intermediate in activity between isoniazid and rifampin on both types of culture. The speed of activity was slow with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…The docking scores confirmed our earlier in vitro studies that moxifloxacin had a better killing activity than gatifloxacin against Mycobacterium tuberculosis H37 Rv [20,21]. The docking studies also yielded that increase in the lipophilicity on either of the positions of the quinolone structure considerably increased the binding affinities.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The docking scores confirmed our earlier in vitro studies that moxifloxacin had a better killing activity than gatifloxacin against Mycobacterium tuberculosis H37 Rv [20,21]. The docking studies also yielded that increase in the lipophilicity on either of the positions of the quinolone structure considerably increased the binding affinities.…”
Section: Resultssupporting
confidence: 84%
“…These resistant strains showed high sensitivity to both moxifloxacin and gatifloxacin (Figure 6). Our earlier in vitro findings on actively growing and persister Mycobacterium tuberculosis H37 Rv, showed that moxifloxacin is considered to have good sterilizing activity in addition to early bactericidal activity [20]. This could be correlated with the higher binding affinity calculated between the mutant and wild type Gyr A receptors and moxifloxacin (-7.9 kcal/mol) when compared to the maximum binding affinity output from gatifloxacin (-7.4 kcal/mol) (Table 1).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations